2007
DOI: 10.1007/s11676-007-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in litter decomposition-temperature relationships between coniferous and broadleaf forests in Huangshan Mountain, China

Abstract: A study was conducted to identify the differences in the decompositions of leaf litter, lignin and carbohydrate between coniferous forest and broadleaf forest at 20°C and 30°C in Huangshan Mountain, Anhui Province, China. Results showed that at 20°C mass loss of leaf litter driven by microbial decomposers was higher in broadleaf forest than that in coniferous forest, whereas the difference in mass loss of leaf litter was not significant at 30°C. The temperature increase did not affect the mass loss of leaf lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The k values for the three broadleaved tree species were also higher than those for the three needle species (Table 3). These results indicated that the litter of broadleaved tree species decomposed more easily than that of coniferous species, consistent with many previous reports (Prescott et al 2000, Kazakou et al 2006, He et al 2007, Freschet et al 2012.…”
Section: Discussionsupporting
confidence: 92%
“…The k values for the three broadleaved tree species were also higher than those for the three needle species (Table 3). These results indicated that the litter of broadleaved tree species decomposed more easily than that of coniferous species, consistent with many previous reports (Prescott et al 2000, Kazakou et al 2006, He et al 2007, Freschet et al 2012.…”
Section: Discussionsupporting
confidence: 92%
“…Berger & Berger, 2014). The differences are often associated with dissimilar lignin and nutrient contentsof leaves and needles (Berger & Berger 2014) and possibly with higher diversity of microbial decomposers in broadleaved than coniferous forests (He et al, 2007). As for woody debris, Shorohova & Kapitsa (2016) commented that the decomposition rate in European forests depends on site moisture andon tree species.…”
Section: Discussionmentioning
confidence: 99%
“…The coniferous forest is the early stage, and the broad-leaved forest is the final stage in the succession trajectories of the forest ecosystems. These forests play an important role in global carbon (C) dynamics, partly due to their high productivity and nutrient turnover (Hughes et al 1999;He et al 2007). There is ample evidence that leaf litter decomposition and the consequent release of nutrients and carbon dioxide are key processes in determining ecosystem nutrient cycling and C flux (Hoorens et al 2003).…”
Section: Introductionmentioning
confidence: 99%